Analysis Of Passenger Service Performance On Ship Crossing Facilities Ro-Ro Air Putih - Muhammad Rizki Romadhan; Guswandi; Faisal Ananda (Civil Engineering Dept, Balikpapan State Polytechnics, 2025)
In recent times there have been many public complaints related to the performance or quality of service at the Ro-Ro Air Puti Bengkalis crossing facility, such as the lack of adequate facilities and infrastructure, the length of time waiting for the ship, and other factors that make passengers less satisfied with the performance provided. The purpose of the study was to analyze how much the level of satisfaction of Ro-Ro Bengkalis users is to determine the level of service performance based on the quality of service obtained and the perception of passenger prices at the Ro-Ro Bengkalis crossing port, so that it is hoped that this research can make a significant empirical contribution to the development of policies to improve service quality at the Ro-Ro Air Putih ship crossing facility. This study uses the CSI (Customer Satisfacyion Index) method to measure passenger satisfaction. Based on the analysis that has been carried out, the performance of passenger services at the Air Putih Ro-Ro ship crossing facility is considered not good, this is based on a CSI value of 48.38% which indicates that passengers / users are less satisfied with the services provided, so it is necessary to improve in a structured and structured manner by related parties, especially on important items such as the availability of health workers and facilities, security officers, timeliness of departure, and discipline of officers, passengers, so that in the future the performance of passenger services on the Air Putih Ro-Ro ship facility can be even more.